Histomorphological Pattern of Cervical Lymphadenopathy (Journal of Enam Medical College, 2013)
Background: Enlarged palpable cervical lymph nodes as a primary presenting sign are very common and may be due to inflammatory lesions and tumors. Correlation between clinical findings and laboratory data is essential in arriving at a diagnosis. In patients presenting with cervical lymphadenopathy, excision biopsy provides material to establish an early diagnosis. We designed this study in our population for histological evaluation of cervical lymph node biopsies that might be important in the management of these patients. Objective: Histopathological evaluation of different diseases involving the cervical lymph nodes in relation to age and sex of the study population. Materials and Methods: It was a cross sectional study conducted in the department of Pathology, Enam Medical College & Hospital, Savar, Dhaka during the period from January 2006 to December 2010. A total of 107 patients were evaluated for specific cause of cervical lymphadenopathy in relation to age and sex. Lymph node biopsies of all patients of both sexes and all age groups were included in the study. Results: Among the 107 subjects 58 (54.2%) were males and 49 (45.8%) were females with a male to female ratio of 1.2:1. The age of the patients ranged from 2 to 85 years with a mean age of 32.68 ± 18.01 years. Of the 107 lymph node biopsies, 34 cases (31.8%) were reactive lymphadenitis, 41 cases (38.3%) were tuberculosis, 2 cases (1.9%) were non-caseous granuloma, 6 cases (5.6%) were Hodgkin lymphoma, 8 cases (7.5%) were non-Hodgkin lymphoma, 12 cases (11.2%) were metastatic neoplasm and 4 cases (3.7%) were other specific lesions. Conclusion: The commonest cause of cervical lymphadenopathy was tuberculosis, followed by reactive lymphadenitis, lymphoma and metastatic neoplasm. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13837 J Enam Med Col 2013; 3(1): 13-17